Efficient screen printed perovskite solar cells based on mesoscopic TiO2/Al2O3/NiO/carbon architecture. (October 2015) - Cao, Kun; Zuo, Zhixiang; Cui, Jin; Shen, Yan; Moehl, Thomas; Zakeeruddin, Shaik M.; Grätzel, Michael; Wang, Mingkui
Abstract: We present efficient perovskite solar cells using a mesoscopic TiO2 /Al2 O3 /NiO/carbon structure as framework. The CH3 NH3 PbI3 -based device with quadruple-layer architecture achieves a power conversion efficiency of 15.03% under AM 1.5G illumination. Detailed investigations show an increased charge collection and reduced charge recombination in this device structure compared to that without NiO interlayer. It is found that these perovskite solar cells exhibit good stability both in dark and under illumination. Graphical abstract: Highlights: Efficient perovskite solar cell using mesoscopic TiO2 /Al2 O3 /NiO/carbon architecture as framework. The CH3 NH3 PbI3 device achieving a power conversion efficiency of 15.03% under AM 1.5G illumination. The perovskite solar cell exhibiting good stability both in dark and under illumination.